Remaking Television: One Day at a Time's Digital Delivery and Latina/o Cultural Specificity. (January 2020) - del Río, Esteban; Moran, Kristin C.
New distribution models have transformed television over the past decade, and Netflix's One Day at a Time (2017–) stands out not only because it is a remake of a classic Norman Lear sitcom, but because it also foregrounds a Cuban American family. Using a radical contextual and relational approach, this study analyzes One Day at a Time from a cultural studies perspective using theoretical tools that arrive from critical Latina/o communication studies. We analyze the first season's 13 episodes to demonstrate how storytelling is modified in the context of digital streaming. In this case, we argue that One Day at a Time offers an alternative to the flattening of difference far too common in Latina/o media. Instead, the show highlights the cultural specificity of this Cuban American family as a form of broad audience appeal as it negotiates sexual identity and immigration discourses within a contemporary social framework.